2020
DOI: 10.2298/abs201024051h
|View full text |Cite
|
Sign up to set email alerts
|

Infection with different strains of SARS-COV-2 in patients with COVID-19

Abstract: The biological diversity of SARS-CoV-2 was assessed by investigating the genetic variations of the spike glycoprotein of patients with COVID-19 in Iraq. Sequencing identified fifteen novel nucleic acid variations with a variety of distributions within the investigated samples. The electropherograms of all identified variations showed obvious co-infections with two different viral strains per sample. Most samples exhibited three nonsense single nucleotide polymorphism (SNPs), p.301Cdel, p.380Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…Genome sequence differences were probably not related to subcultures as the comparison of more than 50 SARS-CoV-2 full-length genomes sequenced in our laboratory showed no significant differences between the sequences from isolates or samples. Genome sequences of the two strains were sufficiently different to hypothesize a dual SARS-CoV-2 infection as it has already been reported [ 18 , 19 ], rather than genome variants related to ongoing evolution of SARS-CoV-2 in the human body [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genome sequence differences were probably not related to subcultures as the comparison of more than 50 SARS-CoV-2 full-length genomes sequenced in our laboratory showed no significant differences between the sequences from isolates or samples. Genome sequences of the two strains were sufficiently different to hypothesize a dual SARS-CoV-2 infection as it has already been reported [ 18 , 19 ], rather than genome variants related to ongoing evolution of SARS-CoV-2 in the human body [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, despite a rapidly growing body of articles, there is almost no information about dual SARS-CoV-2 infection. To our knowledge, the possibility of SARS-CoV-2 double infection or within-patient genetic diversity was discussed in two works [9, 10]. Authors of both provided no information about patients’ medical history, viral subpopulation dynamics during disease progression, and almost no information about clade classification of SARS-CoV-2 analyzed strains.…”
Section: Discussionmentioning
confidence: 99%
“…Hashim et al [9] utilized Sanger sequencing and found double peaks in short (795 bp) fragments of spike protein gene and interpreted it as the presence of double infection in all of the 19 analyzed samples. Unfortunately, the authors’ interpretation of Sanger sequencing data is questionable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations